New possibilities of calculating the volumes of extracted masses in the surface mining of brown coal - Vrublová, Dana; Kapica, Roman; Gibesová, Beáta; Mudruňka, Jaroslav (GeoScience Engineering, 2017)
Brown coal mining companies are looking for ways to manage the mining process as efficiently as possible. The crucial mining technology for brown coal mining in our country, but also in Germany and Poland are wheel excavators. The evolving GNSS technology has enabled designing and implementing systems for determining the spatial position of the excavator wheel. The visualization of the wheel’s spatial position and its real-time motion tracking is performed in the Czech Republic by the KVASoftware Mine Model Program. One of the most important tasks of mining meters is the calculation of the volumes of the extracted masses. The described system performs this task in real-time. This article describes an application that is used to automate volume calculations.